The Effect of Counseling Program for Improvement Psychological Endurance in Excellent Basketball League - Thamer , Jaafar; Muttasher , Feras (Journal of Physical Education, 2022)
The importance of the research lies in designing psychological counseling for improving psychological endurance in advance basketball club players. The research aimed at designing a scale for psychological endurance for basketball excellent league as well as identifying the effect of the program on psychological endurance. The researchers used the descriptive method on (11) basketball players and designed a scale for psychological endurance. The main experiment as well as pre and posttests were applied and the results showed that the counseling program designed by the researchers is effective in improving psychological endurance in basketball players. There are significant differences in some fields.